The effectiveness of fluency building technique in teaching phonic and vocabulary to improve reading outcome in slow learner children - Violetta, Hasan Noor; Rozainee, Khairudin; Wan, Shahrazad Wan Sulaiman; Ng, Alvin Lai Oon * (Malaysian Psychological Association, UKM, 2022)
Slow Learner (SL) is a term that is used to classify children with borderline intellectual disability or those who are mildly intellectually disabled. Research found that slow-learning children are likely to be three times slower in reading rates with general reading comprehension difficulty compared to their faster-learning peers. While standard methods can be improve reading fluency and comprehension, slow-learning children need special attention and creative solutions that will be critical in improving their reading fluency. This research aims to investigate whether phonics and vocabulary Fluency Building techniques can be effectively combined to improve slow-learning children’s fluency. The research was conducted with 15 participants that is children in the first semester of kindergarten at Sekolah Esa and Palm Kids Schools who had been diagnosed with mild or borderline intellectual disabilities divided. The research has found that the Fluency Building technique is an effective approach to support the learning of slow-learning children. This research has illustrated that the cognitive ability of the students is a small hindrance to their reading ability. Hence, these techniques can be incorporated into the individual teaching approaches dedicated to improving the reading fluency of students.